Impact Of Human Activities – River Interaction On Aquatic Insects At Selected Recreational Areas In Northern Peninsular Malaysia - Normi, Norshamiera (2017)
Aquatic insects and public awareness were studied intensively to understand the interaction between human and river in maintaining the ecosystem. Aquatic insects collected from May 2014 to April 2015 from six recreational rivers; were namely Batu Hampar, Titi Hayun, Bukit Hijau, and Sedim in Kedah, Bukit Mertajam and Teluk Bahang in Pulau Pinang were represented by 119 genera of which 23,072 individuals from 69 families and 9 orders. Aquatic insects collected during sampling was dominated by order Ephemeroptera, Diptera and Trichoptera. Ecological indices showed that aquatic insects collected at Batu Hampar River were more diverse, rich and even compared to other rivers. However, biological indices such as Family Biotic Index (FBI), Biological Monitoring Working Party (BMWP) and EPT taxa richness implied water quality at Bukit Hijau River as moderately good to very good. Referring to Water Quality Index (WQI), all selected recreational rivers were categorized into class II (clean) except for Batu Hampar River which fall into class I (very clean) of WQI. The sampling periods were divided into three seasons which were before school holiday, during school holiday season and after school holiday season. Abundance of aquatic insects were differed significantly among the seasons.